Records of the Todt Organization (Organisation Todt) - Daub, Walter (NARA, 1941)
Correspondence, lists and miscellaneous material relating to construction workers and the construction industry in general in Germany. Mostly typescript; contains four small published pieces and one published book: OT-Verträge : Vertragsrecht der Organisation Todt / von Walter Daub. --Wiesbaden : L. Schellenberg, 1944.